Comparing the Efficacy of Oral Pregabalin Premedication with Placebo on Stress Response in Patients Undergoing Laparoscopic Cholecystectomy After Creation of Pneumoperitoneum - Aziz, Iqra; Aatir Fayaz, Muhammad; Usman Mohsin, Muhammad; Kaleem Sattar, Muhammad; Sultan, Atqua; Adnan, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Hemodynamic fluctuations following pneumoperitoneum creation during laparoscopic cholecystectomy pose a challenge in anaesthesia management. Pregabalin, a gabapentinoid, has shown potential in attenuating this stress response. Objective: To compare the effects of oral pregabalin premedication with placebo on heart rate (HR) and mean arterial pressure (MAP) in patients undergoing laparoscopic cholecystectomy. Methodology: This prospective study was conducted at the Department of Anesthesiology, Nishtar Medical University and Hospital, Multan, from June 23, 2023, to December 22, 2023. Sixty patients were randomly assigned to two groups: Group A received 150 mg of oral pregabalin one hour before general anaesthesia, while Group B received a placebo. Standard intraoperative monitoring was used, and HR, systolic blood pressure (SBP), diastolic blood pressure (DBP), and MAP were recorded. Data were analysed using SPSS version 27, and an independent sample t-test was used to compare hemodynamic parameters between the two groups, with a significance level of p<0.05. Results: After five minutes of pneumoperitoneum creation, Group A had significantly lower HR (78.23 ± 5.03 bpm vs. 87.50 ± 5.73 bpm, p<0.001), MAP (91.73 ± 5.06 mmHg vs. 100.79 ± 5.33 mmHg, p<0.001), SBP (121.20 ± 8.34 mmHg vs. 131.57 ± 8.59 mmHg, p<0.001), and DBP (77.00 ± 5.64 mmHg vs. 85.40 ± 5.33 mmHg, p<0.001) compared to Group B. Conclusion: Oral pregabalin premedication effectively attenuates the hemodynamic stress response following pneumoperitoneum creation in laparoscopic cholecystectomy. Its use as a premedication can enhance perioperative hemodynamic stability.